Dating and publication of the Encyclopédie Méthodique (1782– 1832), with special reference to the parts of the Histoire Naturelle and details on the Histoire Naturelle des Insectes - Evenhuis, Neal L. (Zootaxa, 2003)
The background and publication history of Charles-Joseph Panckoucke’s Encyclopédie Méthodique are presented. The Encyclopédie Méthodique represents one of the major scientific publication achievements of all time. Its publisher Panckoucke recruited series editors and contracted contributors, authored and edited contributions, coordinated the first 12 years of production with up to 18 printing presses and 90 staff, and sold the results to subscribers despite financial difficulties, political upheavals, and the inevitable tardiness and even unfortunate demise of contributing authors. Because the Encyclopédie Méthodique is essential to the knowledge of systematics since its natural history dictionaries contained some of the first syntheses of taxonomic knowledge since Linnaeus’ Systema Naturae, this paper presents for the first time accurate dates of publication of all 102 parts comprising the entire Encyclopédie Méthodique. Also included are lists of authors of each dictionary, list of editors of each dictionary, and lists of the original printers contracted to produce the first parts.